2016
DOI: 10.1038/srep27411
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma cell lines retain the genomic and transcriptomic landscapes of primary human cancers

Abstract: Hepatocellular carcinoma (HCC) cell lines are useful in vitro models for the study of primary HCCs. Because cell lines acquire additional mutations in culture, it is important to understand to what extent HCC cell lines retain the genetic landscapes of primary HCCs. Most HCC cell lines were established during the last century, precluding comparison between cell lines and primary cancers. In this study, 9 Chinese HCC cell lines with matched patient-derived cells at low passages (PDCs) were established in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 42 publications
(78 reference statements)
2
52
0
Order By: Relevance
“…87% clonality, Table S1). This is consistent with minimal genomic drift in long-term culture and migration on plastic [34]. Clonal expansion not only produces sufficient DNA for accurate genomic analyses but also provides evidence of viable, proliferating cancer cells—typical of malignancy—rather than non-viable or senescent cells with excessive DNA damage that might be analyzed by single cell methods.…”
Section: Resultssupporting
confidence: 55%
“…87% clonality, Table S1). This is consistent with minimal genomic drift in long-term culture and migration on plastic [34]. Clonal expansion not only produces sufficient DNA for accurate genomic analyses but also provides evidence of viable, proliferating cancer cells—typical of malignancy—rather than non-viable or senescent cells with excessive DNA damage that might be analyzed by single cell methods.…”
Section: Resultssupporting
confidence: 55%
“…[24] A major limiting factor in the use of available cell line is the lack of primary tumor materials for comparative and authentication purposes. [2529] The availability of primary tumor for comparative genomic sequencing analysis with the cell line is important to in identifying potential key genes and for investigating their biological and therapeutic implication in SDC. In this study, the finding of common set of shared mutations between cell line and primary tumor not only provide additional novel genes for investigations but also underscore its faithful representation of donor tumor.…”
Section: Discussionmentioning
confidence: 99%
“…27 In vitro HCC cancer cell lines are relatively inexpensive, allow for seamless high-throughput drug testing, and most importantly, retain genomic and transcriptomic landscapes similar to primary HCCs. 28 Whole genome analyses of 4 newly established HCC cell lines showed that mutations, copy number alterations, and HBV integration were preserved during cell line establishment. 28 However, there is the caveat that although these cell lines harbour driver mutations similar to primary HCCs, they do not retain the same profile of genetic alterations as the…”
Section: Patient-derived Cell Linesmentioning
confidence: 99%